Acquisition and loss of CTX-M plasmids in Shigella species associated with MSM transmission in the UK. Issue 8 (24th August 2021) - Locke, Rebecca K.; Greig, David R.; Jenkins, Claire; Dallman, Tim J.; Cowley, Lauren A.
Abstract : Shigellosis in men who have sex with men (MSM) is caused by multidrug resistant Shigellae, exhibiting resistance to antimicrobials including azithromycin, ciprofloxacin and more recently the third-generation cephalosporins. We sequenced four bla CTX-M-27 -positive MSM Shigella isolates (2018–20) using Oxford Nanopore Technologies; three S. sonnei (identified as two MSM clade 2, one MSM clade 5) and one S. flexneri 3a, to explore AMR context. All S. sonnei isolates harboured Tn7/Int2 chromosomal integrons, whereas S. flexneri 3a contained the Shigella Resistance Locus. All strains harboured IncFII pKSR100-like plasmids (67-83kbp); where present bla CTX-M-27 was located on these plasmids flanked by IS 26 and IS 903B, however bla CTX-M-27 was lost in S. flexneri 3a during storage between Illumina and Nanopore sequencing. IncFII AMR regions were mosaic and likely reorganised by IS 26 ; three of the four plasmids contained azithromycin-resistance genes erm(B ) and mph(A ) and one harboured the pKSR100 integron. Additionally, all S. sonnei isolates possessed a large IncB/O/K/Z plasmid, two of which carried aph(3')-Ib/aph(6)-Id/sul2 and tet(A ). Monitoring the transmission of mobile genetic elements with co-located AMR determinants is necessary to inform empirical treatment guidance and clinical management of MSM-associated shigellosis.